2013
DOI: 10.1590/s0100-69162013000400025
|View full text |Cite
|
Sign up to set email alerts
|

Quality of papaya hybrid grown under different irrigation depths

Abstract: Irrigation is a practice widely used in fruit production in the Brazilian Northeast region, including in the papaya crop in order to increase their productivity. For the purpose of knowing the productive potential of papaya hybrid irrigated, an experiment was carried out in order to evaluate the performance of a papaya hybrid under different irrigations depths. Four irrigation depths (50, 75, 100 and 125% of ETo) were tested and the reference evapotranspiration was calculated by the Penman-Monteith model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
2
4
1
Order By: Relevance
“…It is important to emphasize that full irrigation resulted in the highest SS and SS/TA ratio values in both experiments, with a significant effect for SS in the BA experiment. These results contrast with www.nature.com/scientificreports/ those observed by previous study 57 . They obtained the highest contents of soluble solids in 208 'UENF/Caliman 01' papaya fruits when produced under lower irrigation depths (50% and 75% ETo).…”
Section: Effects Of Partial Root-zone Drying (Prd) Technique On Plant Growth Traits Plant Height Wascontrasting
confidence: 99%
“…It is important to emphasize that full irrigation resulted in the highest SS and SS/TA ratio values in both experiments, with a significant effect for SS in the BA experiment. These results contrast with www.nature.com/scientificreports/ those observed by previous study 57 . They obtained the highest contents of soluble solids in 208 'UENF/Caliman 01' papaya fruits when produced under lower irrigation depths (50% and 75% ETo).…”
Section: Effects Of Partial Root-zone Drying (Prd) Technique On Plant Growth Traits Plant Height Wascontrasting
confidence: 99%
“…However, for all treatments, values of this quality component were satisfactory, being above 10.8 ° Brix, a feature cited by Costa et al (2013) for 'Tainung 1' papaya. As in the present study, Silva et al (2013) found that higher soluble solids contents were obtained in UENF / Caliman 01 papayas when produced under water deficit conditions, i.e., with 50% and 75% ETo.…”
Section: Resultssupporting
confidence: 84%
“…Regarding fruit quality, there are positive responses to water availability, as verified by Silva et al (2013), where the largest cross-sectional and longitudinal diameters of UENF / Caliman 01 hybrid were obtained from irrigation depths of about 108% of ETo, and can be grown in the state of Paraíba hinterland with replacement rate of 100% of ETo, without compromising fruit quality. However, information on the quality of 'Tainung 1' papaya, which is a commercial variety produced under PRD conditions, is scarce.…”
Section: Introductionmentioning
confidence: 85%
“…These results are consistent with Silva et al (2013) and Carvalho et al (2014) that specify the high water demands of the crop. The disequilibrium in water availability in the growth and production phase could affect negatively the papaya final production (Silva et al, 2013). Therefore, the high annual hydric deficiency projected by the scenarios studied here, mainly in the west of the State, will be an important limiting factor to restrict the papaya plantation.…”
Section: Fig Climate Risk Analysessupporting
confidence: 89%